Methods of Cough Assessment and Objectivization - Jakusova, J; Brozmanova, M (Physiological research, 2023)
Cough is one of the most important airway defensive reflexes aimed at removing foreign particles or endogenously produced materials from the airways and provides protection against aspiration. Generally considered, cough is a vital physiological defensive mechanism for lung health. However, in case of cough dysregulation this reflex can become pathological and leads to an adverse influence on daily life. Therefore, it is necessary to effectively evaluate the severity of cough for its diagnosis and treatment. There are subjective and objective methods for assessing cough. These methods should help describe the heterogeneity of cough phenotypes and may establish better treatment by monitoring response to nonpharmacological or pharmacological therapies. It is important to keep in mind that the clinical assessment of cough should include both tools that measure the amount and severity of the cough. The importance of a combined subjective and objective evaluation for a comprehensive assessment of cough has been advocated in the guidelines of the European Respiratory Society on cough evaluation. This review article provides an overview of subjective and objective methods for assessing and monitoring cough in children and adults comparing to animal models. Key words Cough frequency; Cough intensity; Cough reflex sensitivity; Cough monitors; Cough assessment.
Keywords: Cough; reflex; kašel; Lung; Reflex; dospělí; zvířata; plíce; Adult; Humans; Child; dítě; lidé; Animals